(untitled) (Bangladesh Journal of Plant Taxonomy, 2025)
This study aims to examine chromosome morphologies of the genus Centaurea from Türkiye. Chromosome counts were performed during somatic metaphase using squash technique. The clearest metaphase stages were identified, and the chromosomes were analyzed using an imaging system. The chromosome number for C. solstitialis subsp. carneola was found to be 2n=18, while the other taxa were determined to have 2n=16. C. verutum is differentiated from other taxa with the same chromosome number based on its karyotype formula. In conclusion, it can be inferred that the data obtained from karyomorphological studies contribute to the differentiation of taxa. Bangladesh J. Plant Taxon. 32(1): 17-25, 2025 (June)